2020
DOI: 10.1155/2020/3054373
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Factors and Cognitive Function Assessments Associated with Mild Cognitive Impairment Progression for the Elderly

Abstract: Objectives. In this study, we aimed to conduct a 6-year follow-up and acquire a large sample dataset to analyze the most important demographic factors and cognitive function scale variables associated with mild cognitive impairment (MCI) progression for an elderly cohort (age ≥ 60 years old). Patients and Methods. We analyzed the subjects who had participated in a survey in 2011 and were successfully contacted in the later survey in 2017. For each subject, the basic demographic information was recorded, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
2
19
1
Order By: Relevance
“…The MMSE score was 18.0 ± 5.0 for the dementia patients and 25.3 ± 4.6 for the non-dementia individuals and ranged from 5.0-30.0 (p < 0.05). Thus, the dementia patients exhibited lower MMSE scores and education levels and higher mean ages than the non-dementia individuals (Pedraza et al, 2013;Qin et al, 2020). Moreover, the GDS score was higher in the dementia individuals (16.0 ± 6.1, mean ± standard deviation) than in the non-dementia subjects (10.8 ± 6.2).…”
Section: Subject Characteristicsmentioning
confidence: 87%
“…The MMSE score was 18.0 ± 5.0 for the dementia patients and 25.3 ± 4.6 for the non-dementia individuals and ranged from 5.0-30.0 (p < 0.05). Thus, the dementia patients exhibited lower MMSE scores and education levels and higher mean ages than the non-dementia individuals (Pedraza et al, 2013;Qin et al, 2020). Moreover, the GDS score was higher in the dementia individuals (16.0 ± 6.1, mean ± standard deviation) than in the non-dementia subjects (10.8 ± 6.2).…”
Section: Subject Characteristicsmentioning
confidence: 87%
“…This, to some extent, reflects the severe situation of cognition decline among the Chinese population even with differences in the range of participants’ ages or the diagnosis criteria of MCI. The MCI progression factors were characterized as older age and worse income level [ 36 ]. Similarly, a finding from our study showed that participants with MCI and its subtypes clustered with old age, rural area, and lower monthly income level groups.…”
Section: Discussionmentioning
confidence: 99%
“…The following socio-demographic variables were considered as covariates–age, sex, education, race/ethnicity, and income. These variables were known to be associated with MCI among older adults [ 12 , 27 ]. Education was categorized into four groups: less than high school, high school or equivalent, some college including vocational certificate and associate, and bachelors or more.…”
Section: Methodsmentioning
confidence: 99%